2009
DOI: 10.1111/j.1095-8649.2009.02350.x
|View full text |Cite
|
Sign up to set email alerts
|

Food selection of a corallivorous butterflyfish Chaetodon austriacus in the Red Sea, with particular emphasis on size and fish symbionts of corals

Abstract: The exquisite butterflyfish Chaetodon austriacus feeds mainly on Acropora, Pocillopora, Montipora and Stylophora in the northern Red Sea. Large colonies of Acropora are preferred over smaller colonies and other coral genera, whereas avoidance is indicated for corals that are occupied by certain coral-associated gobiid fishes of the genus Gobiodon. It is suggested that, apart from coral identity, colony size and potential repellent effects of particular coral symbionts are both important sources of variation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…They suggested that spatial variation in predation from chaetodontids plays a significant role in the distribution of adult coral populations. This idea seems unlikely considering the findings of Niedermüller et al (2009) and our observations, in which only 11/57 very small colonies of Acropora hyacinthus and A. millepora were ever fed during an observation. These small colonies received <1% (17/2391) of the observed bites.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…They suggested that spatial variation in predation from chaetodontids plays a significant role in the distribution of adult coral populations. This idea seems unlikely considering the findings of Niedermüller et al (2009) and our observations, in which only 11/57 very small colonies of Acropora hyacinthus and A. millepora were ever fed during an observation. These small colonies received <1% (17/2391) of the observed bites.…”
Section: Discussionmentioning
confidence: 68%
“…This species avoided feeding upon Acropora colonies < 400 cm 2 with these colonies consumed in proportions significantly lower than expected given their availability, while it positively selected for all colonies > 400 cm 2 (Niedermüller et al 2009). The factors structuring this avoidance of small colonies are unclear, but are likely to be related to optimal foraging theory.…”
Section: Discussionmentioning
confidence: 81%
“…Butterflyfishes exhibit particularly high levels of dietary specialization (Reese 1977;Hourigan et al 1988;Tricas 1989;Cox 1994;Berumen et al 2005;Pratchett 2005;Niedermüller et al 2009). Chaetodon trifascialis is among the most specialized of all reef fishes and feeds almost exclusively on tabular Acropora throughout its geographical range (Reese 1981;Irons 1989;Alwany et al 2003;Berumen and Pratchett 2006).…”
Section: Corals As Foodmentioning
confidence: 99%
“…Chaetodon trifascialis is among the most specialized of all reef fishes and feeds almost exclusively on tabular Acropora throughout its geographical range (Reese 1981;Irons 1989;Alwany et al 2003;Berumen and Pratchett 2006). Most coral-feeding fishes preferentially consume species from the genera Acropora and Pocillopora (Berumen et al 2005;Pratchett 2005Pratchett , 2007Cole et al 2008;Niedermüller et al 2009), which are also those corals that are most vulnerable to bleaching (Marshall and Baird 2000). Accordingly, many butterflyfishes (especially, C. trifascialis) have disappeared on reefs subject to severe coral bleaching.…”
Section: Corals As Foodmentioning
confidence: 99%
“…Accordingly, within a recovering reef, the average Acropora colony is younger and hence smaller than before bleaching events (McClanahan et al 2008). Territorial butterflyfishes avoid feeding on very small and juvenile colonies (Niedermüller et al 2009; Cole and Pratchett 2011b). This is likely to further increase the chronic predation pressure on less abundant and more fertile, medium- and large-sized Acropora colonies.…”
Section: Introductionmentioning
confidence: 99%